2018
DOI: 10.18549/pharmpract.2018.01.1068
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a survey instrument to measure factors that influence pharmacist adoption of prescribing in Alberta, Canada

Abstract: Objective:Study objectives were to develop a questionnaire to assess factors influencing pharmacists’ adoption of prescribing (i.e., continuing, adapting or initiating therapy), describe use of pre-incentive and mixed mode survey, and establish survey psychometric properties.Methods:Questions were developed based on prior qualitative research and Diffusion of Innovation theory. Expert review, cognitive testing, survey pilot, and main survey were used to test the questionnaire. Six content experts reviewed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Albertan pharmacists do not require a written agreement with a physician to prescribe as in the US model. Furthermore, pharmacists do not require additional training with a physician partner as in the UK model [ 64 ]. National Center for Health Workforce Analysis, sponsored by the Health Resources and Services Administration, projected that between 2012 and 2025 the pharmacist supply, adjusting for new entrants as well as exit from the labor force demand would increase by 16%.…”
Section: Job Market In Developed Countriesmentioning
confidence: 99%
“…Albertan pharmacists do not require a written agreement with a physician to prescribe as in the US model. Furthermore, pharmacists do not require additional training with a physician partner as in the UK model [ 64 ]. National Center for Health Workforce Analysis, sponsored by the Health Resources and Services Administration, projected that between 2012 and 2025 the pharmacist supply, adjusting for new entrants as well as exit from the labor force demand would increase by 16%.…”
Section: Job Market In Developed Countriesmentioning
confidence: 99%
“…Isenor et al described time, staffing, and reimbursement as barriers identified to fully adopting prescribing. Guirguis et al described limitations in the practice environment including staffing [ 29 , 30 ]. While pharmacists are one of the most accessible primary care health care providers, based on the number of patient visits compared with primary care physicians, a limited range of prescribing authority combined with lack of appropriate remuneration potentially impacts patient perception of the pharmacist’s role and the pharmacist’s full adoption of services into practice [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…An existing survey instrument with evidence for reliability and validity was developed by Guirguis and others 19 for the purpose of measuring factors that influence pharmacists' adoption of prescribing in Alberta, Canada. We contacted the authors of that survey instrument and obtained permission to adapt their survey instrument to address our primary objective.…”
Section: Survey Questionsmentioning
confidence: 99%
“…We contacted the authors of that survey instrument and obtained permission to adapt their survey instrument to address our primary objective. For our Likert-type questions, we adapted 3 of the 8 scales with strong evidence for reliability and validity from the survey instrument by Guirguis and others, 19 including questions about self-efficacy, support from the practice environment, and support from interprofessional relationships (for the complete survey, see Appendix 1, available at https://www.cjhp-online.ca/index .php/cjhp/issue/view/ 205). We included additional qualitative open-ended questions to address one of our secondary objectives.…”
Section: Survey Questionsmentioning
confidence: 99%